STRATEGI KOMUNIKASI KOMUNITAS ONE DAY ONE JUZ DALAM MENDORONG MASYARAKAT MEMBACA AL QUR’AN DI KOTA MEDAN - Aulia Rahman; Muhammad Ichsan; Novry Rivaldy; Ahmad Tamrin Sikumbang (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This article aims to find out how the One Day One Juz communication strategy is in encouraging people to read the Qur'an in Medan City. The type of research used in this research is qualitative with a phenomenological approach. Based on the results of the discussion, it is known that the main media used in implementing communication strategies use social media platforms such as Facebook, Twitter, websites, and so on. Based on the interview results, persuasive communication is a technique used by the community to encourage people's confidence in reading the Qur'an. The program efforts carried out by the community include carrying out community education campaigns, holding group activities and discussions, as well as collaborating with educational institutions and youth.